2021
DOI: 10.1038/s41598-020-79833-7
|View full text |Cite
|
Sign up to set email alerts
|

HLA genotype-clinical phenotype correlations in multiple sclerosis and neuromyelitis optica spectrum disorders based on Japan MS/NMOSD Biobank data

Abstract: HLA genotype-clinical phenotype correlations are not established for multiple sclerosis (MS) and neuromyelitis optica spectrum disorders (NMOSD). We studied HLA-DRB1/DPB1 genotype–phenotype correlations in 528 MS and 165 NMOSD cases using Japan MS/NMOSD Biobank materials. HLA-DRB1*04:05, DRB1*15:01 and DPB1*03:01 correlated with MS susceptibility and DRB1*01:01, DRB1*09:01, DRB1*13:02 and DPB1*04:01 were protective against MS. HLA-DRB1*15:01 was associated with increased optic neuritis and cerebellar involveme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 62 publications
0
13
0
Order By: Relevance
“…A notable finding was a strong independent protective effect of DPA1*01:02∼DPB1*03:01, a finding distinct from previously reported DPA1*02:01∼DPB1*11:01 predisposing effects. 16 Of interest, DPB1*03:01 is a high-expression allele 35 and has been involved in susceptibility (not protection) to a number of other autoimmune diseases, such as multiple sclerosis, 36-38 severe aplastic anemia, 39 primary biliary cholangitis, 40 and B27 negative ankylosing spondylitis. 41 By contrast, although HLA class I alleles known to be associated with DRB1*07:01, such as B*57:01, B*44:03, C*06:02, and C*16:01, were increased in the sample uncorrected for DRB1*07:01 (data not shown) as previously reported, 16 all HLA class I association disappeared after controlling for the main DR7 association (data not shown).…”
Section: Discussionmentioning
confidence: 99%
“…A notable finding was a strong independent protective effect of DPA1*01:02∼DPB1*03:01, a finding distinct from previously reported DPA1*02:01∼DPB1*11:01 predisposing effects. 16 Of interest, DPB1*03:01 is a high-expression allele 35 and has been involved in susceptibility (not protection) to a number of other autoimmune diseases, such as multiple sclerosis, 36-38 severe aplastic anemia, 39 primary biliary cholangitis, 40 and B27 negative ankylosing spondylitis. 41 By contrast, although HLA class I alleles known to be associated with DRB1*07:01, such as B*57:01, B*44:03, C*06:02, and C*16:01, were increased in the sample uncorrected for DRB1*07:01 (data not shown) as previously reported, 16 all HLA class I association disappeared after controlling for the main DR7 association (data not shown).…”
Section: Discussionmentioning
confidence: 99%
“…Our findings suggest a possible association between month of birth and risk of NMOSD; however, the evidence is still insufficient to draw a certain conclusion. Because of differences between NMOSD and MS in environmental and genetic risk factors [ 46 , 48 ], it is impossible to apply the suggested seasonal factors to the NMOSD population. Further studies are recommended to elucidate the relation between month of birth and disease development of NMOSD and its seasonal factors.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, HLA-DQA1*102, HLA-DQA1*501, HLA-DQB1*0201, and HLA-DRB1*03 alleles were significantly associated with NMOSD [ 96 , 98 ]. In Japan, Ogawa et al found that HLA-DQA1*05:03 was significantly associated with NMOSD, whereas Watanabe et al reported that HLA-DRB1*08:02 and HLA-DPB1*05:01 were associated with susceptibility to NMOSD and that HLA-DRB1*09:01 was protective against NMOSD [ 99 , 100 , 101 ]. In addition, distinct genetic and infectious profiles in Japanese patients with NMOSD demonstrated that the HLA-DRB1*1602 and HLA-DPB1*0501 alleles as well as infection with Helicobacter pylori and Chlamydia pneumonia were associated with higher susceptibility to AQP4-IgG-seropositive NMOSD [ 102 ].…”
Section: Genetic Susceptibility To Nmosdmentioning
confidence: 99%